Antibacterial activities, proposed mode of action and cytotoxicity of leaf extracts from Triumfetta welwitschii against Pseudomonas aeruginosa - Molly Mombeshora; Stanley Mukanganyama (BMC, 2019)
Abstract Background Pseudomonas aeruginosa has become a main cause of Gram-negative infection, particularly in patients with compromised immunity. High rates of resistance to antibiotics are associated with nosocomial infections caused by P. aeruginosa strains. The search for novel antimicrobials has been necessitated by the emergence of antimicrobial resistance in some bacteria Plant-based antimicrobials has great potential to combat microbial infections using a variety of mechanisms. Triumfetta welwitschii plant roots are traditionally used to treat symptoms of diarrhoea and fever, suggesting that it possess antimicrobial and immunomodulatory effects. Since research investigating antimicrobial properties of the roots of Triumfetta welwitschii has been explored, there is need to investigate the antimicrobial activity of its leaf extracts in order to probe their prospective use as new antimicrobial agents that can be used to combat nosocomial infections. The objective of this study was to evaluate the antibacterial activities, the mode of action and cytotoxicity of T. welwitschii leaf extracts. Method Extracts of T. welwitschii leaves were obtained using eight different solvents, the serial exhaustive extraction method and the cold maceration technique. In vitro antibacterial activity evaluation of the extracts was done on eight bacterial isolates using the broth microdilution method. The mode of action for the most potent extracts was investigated using the rhodamine 6G efflux assay and the propidium iodide-based membrane damage assay. Toxicity of the extracts was evaluated using the haemolytic and MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assays. Results The results showed that acetone, ethanol and dichlorometane: methanol extracts had the most potent antibacterial activities against Pseudomonas aeruginosa (ATCC 27853). All three extracts caused membrane disruption of P. aeruginosa as shown by nucleic acid leakage. All three extracts were unable to inhibit efflux pumps. Conclusion The presence of antibacterial activities and low toxicity shown by the extracts indicates that the plant may be a source of effective antibacterial against some bacterial infections caused by P. aeruginosa. The disruption of membrane integrity is one possible mode of action of antibacterial activity of the potent extracts.